(untitled) (Matra Pembaruan: Jurnal Inovasi Kebijakan, 2021)
In general, the hospital outpatient registration queues have problems with long and convoluted waiting times. This study aims to see the extent to which the application of the online registration service system at RSUP Dr. Sardjito and the factors that influence the application of the online registration application service system at RSUP Dr. Sardjito. This research method uses descriptive qualitative research. Data collection techniques through interviews, observation, and documentation. The results of this study indicate that the application of the online registration application service system at Dr. Sardjito is quite running optimally. Judging from simple aspect, transparency and fairness are optimum, but the aspect of participation, accountability, and sustainability are not optimum. The simplicity of the online registration application is easy and fast, so it can reduce queues at manual registration pockets. Transparency in information disclosure has been carried out through social media, websites, applications, and officers. Justice is viewed from the ability of different patients in terms of ability to use applications and financial capabilities. Meanwhile, participation in delivering information on application use directly and information banners is still few and does not contain detailed information. Accountable online registration application shows the performance of officers experiencing obstacles in providing feedback on verification of patient files. Sustainable, related to the queuing system at the polyclinic service, there is no queue number. factors that influence the application of online registration applications, namely the commitment factor RSUP Dr. Sardjito regarding policies, use of applications, and facilities and infrastructure.